Wind power integration in Iceland : impacts on the Icelandic regulating power market - Michel, Felix Rolf 1991- (2017)
Electricity production in Iceland today is almost entirely renewable by utilizing geothermal and hydropower resources. In recent years yet another renewable energy technology became center of the debate: Wind power. By experience of other countries such as Germany and Denmark it is known that wind power integration can have adverse effects on the reliability of the power system, such as increased balancing requirements for supply and demand, transmission constraints and the efficiency of operations of power plants using other production technologies. The focal point of this thesis is the impact of the forecast error of wind power on balancing requirements. Such an error has to be resolved in real time by reserves on the regulating market. Therefore future scenarios of forecast errors after wind integration are modelled, in order to assess whether or not the current legal regulating power reserve of 40 MW should be adapted or not considering a wind power project with 203 MW in a single and dispersed power plant case. It was found that if a 203 MW power plant is to be integrated reserves have to be adapted and operation of the power system will become substantially more expensive. Savings can be made in terms of excess reserve need and associated costs if wind power plants are geographically dispersed rather than concentrated in one single area. Used commercially